Prevalence, awareness and control of hypertension in rural areas in Selangor and Perak - Saud Gany, Siti Liyana; Shahar, Mohammad Arif; Sukor, Norlela; Omar , Ahmad Marzuki; Ab Wahab, Norasyikin; MY, Yusniza; Chong , Kuck Meng; Md Zain, Rabizah; Long , Kha Ching; Mohd Razali, Amyliation; Zainuddin, Noradilah; Mat, Nurul Hani; et al. (ASEAN Federation of Endocrine Societies, 2015)
Abstract The aim of this study was to describe the prevalence, awareness and control of hypertension in the rural population of Perak and Selangor.